Effect of PjBL Model of Diorama Project Making on Student's Creative Thinking Ability and Curiosity on The Matter of Biodiversity - Muliawati, Septia; Wahyuningsih, Daru; Khasanah, Annisa Nur (Journal of Biology Learning, 2023)
This research aims to see the influence of the PjBL model for making dioramas on: (1) Creative Thinking Ability; (2) Curiosity on biodiversity material. This research uses a quasi-experimental quantitative research design, using a group design posttest-only. The sample in this study was class VIIB (control) with a total of 30 students and class VIIG (experiment) with a total of 32 students at SMPN 3 Sukoharjo, Central Java, Indonesia in the 2022/2023 academic year. Data collection on creative thinking abilities was carried out using the test method esssay and for curiosity using a non-test in the form of a questionnaire. The results of the research state that: (1) students' creative thinking abilities using the PjBL model have a significant effect compared to students using the conventional model taught at school. The average score for each class was 73.20 (experimental); 63 (control); (2) curiosity (curiosity) with the PjBL model also has a significant effect compared to students who use the conventional model taught at school with an average score of 70.97 (experiment); 64.91 (control).